Simultaneous Detection of Multiple Point Mutations Using Fluorescence-Coupled Competitive Primer Extension - Sascha Fauser; Bernd Wissinger (BioTechniques, 1997)
We report the development of a method for the simultaneous genotyping of several distinct nucleotide positions by means of fluorescence-coupled competitive primer extension. We demonstrate the application of this method for the simultaneous detection of three point mutations in the human mitochondrial genome, at nucleotide positions 3460, 11778 and 14484, which account for about 90% of cases with Leber’s hereditary optic neuropathy. mtDNA fragments encompassing these nucleotide positions are initially amplified in a multiplex PCR assay. Genotyping is then carried out by a simultaneous primer extension assay using wild-type-specific (FAM-labeled) and mutant-specific (JOE-labeled) oligonucleotides. Primer extension products are separated on a 6% polyacrylamide/8 M urea gel on a fluorescence DNA sequencer. Patients’ genotypes can be derived from the peak color of the different-sized extension products. As little as 10% mutant DNA can be detected in heteroplasmic mixtures of wild-type and mutant mtDNA, a degree that is sufficient for routine clinical practice.